1996
DOI: 10.1042/bj3150989
|View full text |Cite
|
Sign up to set email alerts
|

Bovine inositol monophosphatase: enzyme—metal-ion interactions studied by pre-equilibrium fluorescence spectroscopy

Abstract: Stopped-flow fluorescence spectroscopy has been used to determine the on-rate (kass) and the off-rate (kdiss) for the equilibrium between inositol monophosphatase and Mg2+ ions. The dissociation constant (Kd) for the equilibrium calculated from these constants suggests that the ions interact at site 1 on the enzyme with a Kd typically around 450 microM, close to values determined by equilibrium studies (270-300 microM). The affinity of this site on the wild-type enzyme for Mg2+ ions increases as the pH is incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 30 publications
1
7
1
Order By: Relevance
“…The effect found for pH on the affinity of Mg2 + for site 1 is in close agreement with values obtained by stopped-flow fluorescence studies [18] suggesting that the same site is examined by both techniques, although the latter studies used pyrene-labelled protein. The effect of pH on the affinity of Mg" at site 2 is very close to those found for the effect of pH on the K, for this ion [7] supporting the concept that the signal changes observed at 220 nm are due to metal ion interaction at site 2, i.e.…”
Section: Discussionsupporting
confidence: 76%
“…The effect found for pH on the affinity of Mg2 + for site 1 is in close agreement with values obtained by stopped-flow fluorescence studies [18] suggesting that the same site is examined by both techniques, although the latter studies used pyrene-labelled protein. The effect of pH on the affinity of Mg" at site 2 is very close to those found for the effect of pH on the K, for this ion [7] supporting the concept that the signal changes observed at 220 nm are due to metal ion interaction at site 2, i.e.…”
Section: Discussionsupporting
confidence: 76%
“…We analyzed the event I by performing one independent MSM analysis per subunit (see Methods), which provided remarkably consistent kinetic and affinity estimations between the monomers ( Table 2 ). In quantitative terms, the standard free energy of binding is computed to be −3.8 ± 0.1 kcal/mol, slightly higher than previous dialysis (−4.8 kcal/mol) 22 and fluorescence (−4.6 kcal/mol) 34 experiments. There are no available crystal structures containing only one Mg 2+ bound, however, in binary or ternary complexes Mg-I appears coordinated to three protein residues (Glu70, Asp90, Ile92) and three water molecules.…”
Section: Resultscontrasting
confidence: 57%
“…Only in 4 trajectories out of more than 5000, Mg-I evolved to the crystallographic position with an RMSD lower than 1 Å. Thorne et al . performed stopped-flow fluorescence spectroscopy studies to determine association and dissociation constants for Mg-I and II 34 . The study showed a slow increase in fluorescence after a rapid binding of Mg-I, suggesting that Mg-I binding is followed by a subtle structural rearrangement in the microenvironment of site I.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous approaches, such as enzyme kinetics , site‐directed mutagenesis (e.g. H217Q and C218A) and spectroscopic studies , have been performed to characterize the Li + ion binding site in IMPase. It has been proposed that the Mg2 site is responsible for Li + inhibition.…”
Section: Introductionmentioning
confidence: 99%